Potential carbon stock distribution of mangrove and synergistic effect of ecosystem services in China - Shuhao Liu; Shuai He; Shang Chen (Ecological Indicators, 2025)
Mangroves have remarkable carbon stock capabilities and provide numerous ecosystem services. However, detailed information regarding the distribution of carbon stocks and the trade-offs or synergies among mangrove ecosystem services remains limited. In this study, we first modeled mangrove potential habitat distribution in China using the species distribution model. Subsequently, we quantified the potential carbon stock of whole-tree mangroves within habitat patches through the empirical model. Finally, we evaluated the relationship between carbon sequestration and water quality regulation using the generalized additive model. Our results demonstrated that tree-based algorithms exhibited high predictive accuracy. The provinces of Hainan and the Pearl River estuary in Guangdong were identified as having higher habitat suitability. The predicted northernmost boundary of mangrove distribution was at 28.26°N. The potential carbon stock displayed significant spatial heterogeneity, with higher values in the south and lower in the north. The average potential carbon stock of whole-tree mangroves in China was 198.85 Mg/ha, with above-ground and below-ground carbon stocks averaging 66.28 Mg/ha and 132.57 Mg/ha, respectively. Temperature annual range was identified as the most critical factor influencing mangrove potential carbon stock distribution, followed by sea surface salinity, mean temperature of the driest quarter, sea surface dissolved oxygen, and mean temperature of the wettest quarter. A synergy was observed between carbon sequestration and water quality regulation within mangrove ecosystems. This synergy intensified when carbon stock exceeded 200 Mg/ha, but weakened when water transparency surpassed 9 m. These findings offer large-scale maps of mangrove carbon stocks and can inform strategies for sustainable mangrove management and climate change mitigation.